2019
DOI: 10.1016/j.buildenv.2019.106335
|View full text |Cite
|
Sign up to set email alerts
|

A tracing method of airborne bacteria transmission across built environments

Abstract: A B S T R A C TDisease transmission across built environments has been found to be a serious health risk. Airborne transmission is a vital route of disease infection caused by bacteria and virus. However, tracing methods of airborne bacteria in both lab and field research failed to veritably express the transporting process of microorganism in the air. A new tracing method of airborne bacteria used for airborne transmission was put forward and demonstrated its feasibility by conducting a field evaluation on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Non-respiratory fomites in virally infected animals are readily aerosolized and airborne [ 40 ]. Also, genetically traced and aerosolized Escherichia coli has been demonstrated in adjacent homes demonstrating airborne transmission between built environments [ 41 ]. Certainly, some human activities and/or engineering solutions may impart airborne transmissibility to traditionally non-airborne diseases, but what activity, to what degree, and what is the clinical outcome?…”
Section: Discussionmentioning
confidence: 99%
“…Non-respiratory fomites in virally infected animals are readily aerosolized and airborne [ 40 ]. Also, genetically traced and aerosolized Escherichia coli has been demonstrated in adjacent homes demonstrating airborne transmission between built environments [ 41 ]. Certainly, some human activities and/or engineering solutions may impart airborne transmissibility to traditionally non-airborne diseases, but what activity, to what degree, and what is the clinical outcome?…”
Section: Discussionmentioning
confidence: 99%
“…Simplifying the transmission process of pathogens by defining them as particles or gaseous pollutants is an effective method, however, ignoring the biological characteristics of microorganisms may prevent researchers from understanding the migration of pathogens. In Li et al (2019a) investigation, they used a tracing method to analyze the bacteria transmission in the building environment. It can be divided into three steps in their research: Culturing and filtering the suitable bacteria; Aerosolizing the bacteria particles and conveying into measuring environment; Analyzing the airborne transmission of E. coli by using PCR.…”
Section: Epidemic Theories and Experimental Methodsmentioning
confidence: 99%
“…A previous study by also found that the total bacterial count and total fungal count were higher in ACSU Malaysian mosques compared with non-ACSU mosques. The airborne disease infection across the built environment can be spread by bacteria and virus (Li et al, 2019). A study by Zock et al, (2002) on dampness at home found that indoor microbe growth had a negative impact on adult asthma.…”
Section: Indoor Air Contaminantsmentioning
confidence: 99%